Geometrie van afstraatse laaigebiede met spesifieke verwysing na kleinhandel - Wepener, Daniel Adriaan (2014)
M.Ing. (Transport Engineering) === The background to goods loading in South-Africa are briefly discussed. Retail are classified and distinction are made between six different retail types. Goods vehicles are also classified and a design rigid and articulated goods vehicle (for retail) are determined. The results of the surveys at retail outlets are discussed and the characteristics of goods vehicle movement for example trip generation rates, typical total loading times, service times and goods vehicle composition at the different retail types are dealt with. Regression curves has been calculated for goods vehicle arrivals against trading area. Multiple channel queuing theory is used to determine the loading space requirements for the different types of retail. Theoretical methods .to describe the vehicle track and swept paths during maneuvering is dealt with and turning circle templates for the identified design vehicles are developed. Dimensions of a typical loading area are determined using the templates. The dimensions has also been verified with practical maneuvering tests involving two rigid and two articulated goods vehicles. The maneuvering tests showed that the driving (maneuvering) capabilities of a driver are playing a major role in the loading area needed. The basic principles involved when designing a loading dock are lastly briefly discussed.